Adobe ColdFusion Anthology Clear and Concise Concepts from the Fusion Authority - Michael, Dinowitz; Dinowitz, Judith; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
Adobe ColdFusion remains one of today$1 (Bs significant Web services tools and frameworks, and stands to become even more important as a possible primary tool for cloud development as well. As important as ColdFusion is and continues to become, we thought it would be a good idea to tap the leading authority on ColdFusion, the Fusion Authority. We asked this community to compile the most important issues in their developer and user experiences into one single volume$1 (Ban anthology of the most current technical articles published in the Fusion Authority Quarterly Update. In it, you$1 (Bll get the following: The best and brightest ColdFusion expertise available today, from inside and outside of Adobe The most up-to-date content with the latest releases of ColdFusion Case studies and instances where ColdFusion is used in cloud-based development Rather than take a soup-to-nuts approach that covers every single topic, including those that most people have learned already, this book takes specific items of interest and explains them so that you can hit the ground running, rather than having to wait until you$1 (Bve read the entire book.s
ColdFusion Fundamentals -- Working with Application.cfc -- Application.cfc Reference -- From User-Defined Functions to ColdFusion Components -- onMissingTemplate()$1 (BError Handler and So Much More -- (3z(BSay What?(3y (BHandling Unknown Messages with onMissingMethod() -- Document Creation in ColdFusion -- PDF Support in ColdFusion -- Image Processing in ColdFusion -- Essentials to Server Productivity -- Tuning Your Java Virtual Machine: Finding Your Ideal JVM Settings Through Metrics Log Analysis -- The Shoemaker and the Asynchronous Process Elves -- Asynchronous Gateways Step-by-Step -- You Might Have a Performance Bottleneck If... -- Communication and Integrating with Other Technologies -- An Introduction to Consuming and Deploying Web Services in ColdFusion -- Web Services and Complex Types -- Type Validation When Returning an Array of Components -- Sending E-mail the Right Way -- ColdFusion and Microsoft Exchange -- BlazeDS -- Object-Oriented Programming (OOP) -- Object-Oriented Programming: Why Bother? -- The Object-Oriented Lexicon -- Design Patterns: Exposing the Service Layer -- Beans and DAOs and Gateways, Oh My! -- SOA for the Rest of Us -- How Base Classes Can Help You Generate Your Applications -- ColdFusion Frameworks -- An Introduction to Frameworks -- Fusebox 5 Fundamentals -- Mach-II Fundamentals -- Model-Glue Fundamentals -- ColdSpring Fundamentals -- Reactor Fundamentals -- Developing Applications with Transfer -- FW/1: The Invisible Framework -- Designing the User Interface -- Separating Layout from Logic -- Creating Dynamic Presentations in ColdFusion -- Working with JSON and cfajaxproxy -- Prototyping for Interface Driven Architecture: Easing the Transition from Prototype to Application -- Development Tools -- Turbo Charging Eclipse -- An Introduction to ColdFusion Builder -- The ColdFusion Debugger Explained: Interactive Step Debugging for ColdFusion 8 and 9 -- Getting Started with Subversion -- Subversion in the Workflow -- Advanced Subversion -- Automating Your Development with Ant.s
Keywords: Computer science; Computer Science; Computer Science, general